Czego boją się nastolatkowie? O komentarzu społecznym w horrorze południowokoreańskim na przykładzie serii „Yeogo Goedam” - Martyna Halor (Studia Filmoznawcze)
Korean teenagers in the ‘Yeogo Goedam’ series struggle with educational and social issues, showing school as a place of pressure and violence. The films, from 1998 to 2021, examine the image of education, showing its pathological aspects. Peer violence and pressure for school achievement lead to unhealthy competition, reflecting Confucian culture and social hierarchy. Patriarchal values and expectations of the environment reveal adolescent frustrations, lead to aggression and sometimes to final acts. The characters’ narratives are analysing their identity, which is just forming. Suicide, which is one of the main themes in ‘Yeogo Goedam’, is a pretext for the appearance of fantastic elements in the form of the ghosts of deceased classmates, which symbolise the trauma of both the individual and the educational system in South Korea. ‘Yeogo Goedam’ series encourage reflection on the impact of traditional values on contemporary Korean society and the effects of educational and peer pressure.